Efficacy and Safety of Eculizumab in the Treatment of Transplant-Associated Thrombotic Microangiopathy: A Systematic Review and Meta-Analysis - Zhang, Rui; Zhou, Meng; Qi, Jiaqian; Miao, Wenjing; Zhang, Ziyan; Wu, Depei; Han, Yue (Frontiers in Immunology, 2021)
BACKGROUND: Transplant-associated thrombotic microangiopathy (TA-TMA) is a dangerous and life-threatening complication in patients undergoing hematopoietic stem cell transplantation (HSCT). Eculizumab has been used in the treatment of TA-TMA, and several studies have confirmed the benefit of Eculizumab in patients with TA-TMA. However, the results remain controversial. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of Eculizumab for TA-TMA. MATERIALS AND METHODS: We searched PubMed and Embase for studies on the efficacy and safety of Eculizumab in TA-TMA patients. Efficacy outcomes consisted of overall response rate (ORR), complete response rate (CRR), and survival rate at the last follow-up (SR). Safety outcomes were adverse events (AEs), including infection, sepsis, impaired liver function, infusion reactions, and death. RESULTS：A total of 116 patients from 6 studies were subjected to meta-analysis. The pooled estimates of ORR, CRR, and SR for TA-TMA patients were 71% (95% CI: 58-82%), 32% (95% CI: 11-56%), and 52% (95% CI: 40-65%), respectively. Only one patient presented with a severe rash and infection was the most common AEs. The main causes of death were infection and GVHD. CONCLUSION: Current evidence suggests that Eculizumab improves SR and ORR in patients with TA-TMA and that Eculizumab is well tolerated. However, the number of studies is limited, and the findings are based mainly on data from observational studies. Higher quality randomized controlled trials and more extensive prospective cohort studies are needed.